Microestrutura do cobrimento de concretos com altos teores de escória e cinza volante ativadas por cimento portland e cal hidratada - Brizola, Rodrigo Matzenbacher (2007)
In the history of the concrete structures there was a time in which the mechanical resistance was the most important property for the designers. However due to amount of pathologies in the concrete structures and your respective worn-out amounts in recovery, other feature is being prioritized: the durability. And for environmental reasons as global heating, pollution and the raw materials decrease, the sustentability is prioritized. Aiming at collaborate to these factors these paper has as objective analyzes the microstructure of the covercrete with substitution in mass of 90% of cement for mineral additions. Were researched three types of concretes reference concrete (100%CPV-ARI), concrete with 70%Slag+20%FlyAsh and other similar mixture with addition of 20% of hydrated lime with the intention of partially restoring the hydroxide of calcium consumed by the pozzolanics reactions - named respectively of R, EV and EVC. Aims at, more specifically, to establish the differences microstructures of the covercrete of the prototypes(beams-70x20x15cm), through the tests of combined water, x-ray diffraction and scanning electron microscopy. For comparison effect, compressive strength test were also accomplished in molded cylinders(10x20cm) and cured in humid camera and in the cylinders(10x20cm) extracted of the cured prototypes in environmental conditions after 7 days of humid cure. Were studied three relationships a/ag: 0.40, 0.60 and 0.80 for the concrete R and 0.30, 0.40 and 0.50 for the concretes with additions, obtaining resistance between 20 and 70MPa. The tests of the microstructure were accomplished in the 91 and 300 days, with samples starting from the surface of the prototypes, in layers, in the depths of: 0-1.0cm(C1), 2.0-3.0cm(C2) and 4.5-5.5cm(C3). Evolution of the strength was accompanied in the ages of 28, 91, 182 and 300 days. Results were analyzed in equality of a/ag and compressive strength. For a/ag 0.40 and 0.50, to 28 days of age, in relation to reference concrete, the strength of the concrete EV was 54.0% on average of this, and the concrete EVC it was 68.5%. In the final age of 300 days, the percentile are of 72.5% and 76%. In both tests ages, with the increase of the depth of the layer occurs: decrease in the intruded volume total mercury, decrease in the tenor of combined water for the reference concrete and increment in the concretes with additions, decrease in the intensity of pick of the hydroxide of calcium in the three mixtures, decrease in the intensity of pick of the hydrated silicate for the reference concrete and increment in the concretes with mineral additions. Analysis on scanning electron microscopy showed refinement in the size of the grains, larger compact and uniformity in the mixtures with additions